(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
Annotation. Social support for veterans of various categories is one of the important directions of the state social policy of the Russian Federation. The presence of the institute of social protection for these categories of citizens stabilizes the economic development of the country, and the material condition of these citizens. In addition, the issues of social protection of veterans are conditioned by the objective need of society for an effective system to ensure the protection of the state from encroachments from other states.